The Teacher’s Competency Test In Aswering Education Quality In Indonesia - Jarkawi Jarkawi; Laelatul Anisah; Eka Sri Handayani; Akhmad Rizkhi Ridhani (Pancaran Pendidikan, 2017)
Teacher’s competence was asked the question, The teacher is the key to get the Education quality in Banjarmasin. Answering the quality of education is to see the teacher performance problems.The etnografi method was describing of the teacher characteristic and phenomenon of pedagogical competence and professional competence through qualitative approach toward the group of the teacher with qualitative design, to identification group of a teacher. The data stated by Education Department of Banjarmasin. The participants were 99 teachers; 24 male and 75 female teachers. The data took by observation, interview and document. The resulted; the teacher competency test quality; Part-time teachers 28.28%, rank and class <IV / a 54 545%, Chronological age <53 years of 67.67%, not certified 33.33%, Education <S-1 20:20%, private school 24.24%, Non S-1 guidance and counseling 24.24% , graduates under 2005 59.59%, Pedagogic value <60 97.97%, professional value <65 55 545%.From deep interview; the teacher lack of reading books and browsing, they also lack independence to enhance their competence, out of date the technology, over 150 student-teacher ratios, guidance and counselling are considered public, cite the extra hours for subjects, the teaching profession is no longer their eager self